2016
DOI: 10.1038/srep29151
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte polarization in children with falciparum malaria: relationship to nitric oxide insufficiency and disease severity

Abstract: We earlier established that nitric oxide (NO) is protective against severe malaria and that arginine and NO levels are reduced in malaria patients. We now show that an M2-like blood monocyte phenotype is significantly associated with hypoargininemia, NO insufficiency, and disease severity in Tanzanian children with falciparum malaria. Compared to control children (n = 106), children with moderately severe (n = 77) and severe falciparum malaria (n = 129) had significantly higher mononuclear cell arginase 1 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 62 publications
(120 reference statements)
8
38
1
Order By: Relevance
“…Instead, decreased arginine and citrulline appearance seem to be primarily responsible for plasma arginine depletion. Our results do not directly contradict prior observations of increased host-and parasitederived arginase activity [2,7,10]; increased arginase activity may be required to preserve the rate of conversion of plasma arginine to ornithine in the setting of low arginine levels. However, our mouse model results demonstrate that any increase in arginase activity is secondary to the major effect of decreased arginine and citrulline appearance.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Instead, decreased arginine and citrulline appearance seem to be primarily responsible for plasma arginine depletion. Our results do not directly contradict prior observations of increased host-and parasitederived arginase activity [2,7,10]; increased arginase activity may be required to preserve the rate of conversion of plasma arginine to ornithine in the setting of low arginine levels. However, our mouse model results demonstrate that any increase in arginase activity is secondary to the major effect of decreased arginine and citrulline appearance.…”
Section: Discussioncontrasting
confidence: 55%
“…Host arginase could also contribute to arginine depletion via intracellular activation by cell-free heme [8] or via direct release into plasma during parasite-mediated hemolysis. Consistent with this hypothesis, increased plasma arginase activity has been associated with severe malaria in studies of Indonesian adults [2], Malian children [9], and Tanzanian children [10]. The latter study also demonstrated elevated peripheral blood mononuclear cell arginase 1 messenger RNA expression [10].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Luty et al found remarkably similar correlations with parasitemia and plasma IL-10, TNF, and IL-12p70 levels among Gabonese children with uncomplicated and severe malaria (40). Weinberg et al also demonstrated similarly elevated plasma levels of IL-10 in Tanzanian children with moderately severe and severe malaria, with IL-10 levels showing a significant correlation with disease severity as well as monocyte polarization toward an M2 phenotype with high levels of arginase 1 and low levels of NOS2 expression (which may contribute to NO insufficiency and oxidative stress) (41). Collectively, these observations suggest that oxidative stress related to heme and/or hemozoin toxicity to phagocytes may enhance IL-10 production while downregulating IL-12 activity (42).…”
Section: Cd16mentioning
confidence: 85%
“…89 Increased arginase activity has also been demonstrated in monocytes of the M2 phenotype in children with falciparum malaria. 90 However, in all the above studies concerning the role of NO in severe malaria, microvascular permeability was not directly measured. The readouts were reactive hyperemiaperipheral arterial tonometry, which is more a measure of vascular tone, and gaseous exchange that could be affected by perfusion.…”
Section: Host Inflammatory Mediatorsmentioning
confidence: 99%